Fostering Self-efficacy for Future Physics Teachers: Recommendation of Future Direction of Teacher Education Institutions - Efwinda, Shelly; Haryanto, Zeni; Sulaeman, Nurul Fitriyah (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2024)
Self-efficacy in teaching is essential for pre-service teachers, and its development needs to be started as soon as possible. This research is descriptive research that aims to recommend policies that can be carried out by universities, faculties, and study programs related to the development of pre-service physics teachers' self-efficacy in teaching. The research participants were 113 pre-service physics teachers in one of the teacher education institutions in Indonesia. The research instrument used was an open-ended question questionnaire totaling eight questions, which explores self-efficacy in three aspects, namely general definitions, influencing factors, and lecture activities that can increase teaching self-efficacy. The answers of pre-service physics teachers are grouped based on the study program's authority, faculty, or university. The results show that self-efficacy in teaching is influenced mainly by 1) the mastery experiences, 2) the mastery of content knowledge, 3) social persuasion, and 4) the mastery of pedagogical knowledge. Based on these results, it is necessary to have a policy by the Universities, Faculties, and Study Programs related to the development of self-efficacy in teaching. Policies needed from universities and faculties are to increase the number and length of teaching practice for pre-service teachers. The policy required from the study program is self-efficacy integration in courses, especially courses related to teaching practice. In addition, the study program also needs to make rules or guidelines for lecturers who teach subjects related to teaching practice courses, to provide feedback and reflection, and strengthen teaching practice activities for pre-service teachers.